Fungal spores in four catholic churches in the metropolitan area of Monterrey, Nuevo León State, Mexico – First study - Rocha Estrada, Alejandra; Torres, Elizabeth; Vázquez, Marco Antonio; Piñero, Jorge Luis; Lucio, Marco Antonio; Martínez, Sergio Manuel (2015)
Introduction. About 500,000 species of fungi have been described to-date, although an estimated between 1 – 1.5 million species may occur. They have a wide distribution in nature, contributing to the decomposition of organic matter and playing a part in the biogeochemical cycles of major nutrients. A small number are considered pathogens of animals and plants. There is ample historical evidence that certain types of allergies are associated with fungi; exposure to fungal allergens occurs in both outdoor and indoor spaces. Many indoor allergens are the same as those found outside buildings, entering through windows and doors, ventilation systems, or through cracks or other fissures in the walls. Objective. To determine the diversity and abundance of fungal spores inside four churches in the metropolitan area of Monterrey city in Mexico. Materials and methods. The study was carried out from July 2009 – January 2010 using a Hirst type volumetric collector (Burkard Manufacturing Co Ltd). Results. A total of 31,629 spores from 54 taxa were registered in the four churches. The building that showed the highest amount of spores was the Santa Catarina Mártir Church with 12,766 spores, followed by Cristo Rey with 7,155 and Nuestra Señora del Roble with 6,887. Regularly high concentrations of spores were recorded from 14:00 – 20:00 hours. The highest concentration value was observed at the church of Santa Catarina Mártir at 16:00 hours with 1153 spores/m3 air. Conclusions. The most abundant spores in the four churches studied corresponded to Cladosporium, the Aspergillus/Penicillium complex, Coprinus, Ganoderma, Curvularia and Ustilago.